2008
DOI: 10.1177/154405910808700420
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride and Casein Phosphopeptide-Amorphous Calcium Phosphate

Abstract: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) slows the progression of caries and remineralizes enamel subsurface lesions. The aim of this study was to determine the ability of CPP-ACP to increase the incorporation of fluoride into plaque and to promote enamel remineralization in situ. Randomized, double-blind, cross-over studies involved mouthrinses and dentifrices containing CPP-ACP and fluoride. The mouthrinses were used for 60 sec, three times/day for 5 days, and supragingival plaque was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
311
1
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(350 citation statements)
references
References 17 publications
19
311
1
19
Order By: Relevance
“…The crystal growth during remineralization has the same pattern as crystal growth during amelogenesis 27,28) . Microradiography has shown that CPP-ACP tends to remineralize throughout the lesion even in the presence of fluoride 29) .…”
Section: Discussionmentioning
confidence: 99%
“…The crystal growth during remineralization has the same pattern as crystal growth during amelogenesis 27,28) . Microradiography has shown that CPP-ACP tends to remineralize throughout the lesion even in the presence of fluoride 29) .…”
Section: Discussionmentioning
confidence: 99%
“…6 If adequate amounts of salivary or plaque calcium and phosphate ions are available, the remineralization of previously demineralized enamel can be promoted by fluoride ions. 7 CPP-ACP, which is derived from milk casein, can also be used for remineralization. It has been shown that CPP-ACP increases the levels of calcium and phosphate ions significantly in supragingival plaque and promotes the remineralization of enamel subsurface lesions in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Como não há veículos para utilização do xilitol em mamadeiras ou para crianças pré-escolares e muito jovens 7 , as gomas de mascar e balas contendo xilitol podem ser utilizadas seguramente por mulheres grávidas e mulheres que estão amamentando 22 . O complexo fosfopeptídeo de caseína -fosfato de cálcio amorfo (CPP-ACP) tem sido amplamente estudado e considerado por diversos autores como um meio eficaz de prevenção da doença cárie e da erosão dental 12,[23][24][25][26] , visto a possibilidade de utilização de produtos à base de cálcio e fosfato na tentativa de aumentar a supersaturação destes elementos na saliva e biofilme. Constatou-se que as soluções ácidas tornam-se menos erosivas quando adicionadas de maior concentração destes dois componentes 27 .…”
Section: Figura 2 Distribuição Das Médias Do Ph Salivar Utilizando Ounclassified
“…Outros agentes modificadores também vêm sendo incorporados às gomas de mascar pelos seus fabricantes com o objetivo de minimizar o potencial erosivo da estrutura dentária, como o complexo fosfopeptídeo de caseína -fosfato de cálcio amorfo (CPP-ACP) 11 . Esses compostos à base de CPP-ACP foram lançados recentemente no mercado, com promissor potencial anticariogênico e cariostático pela liberação de íons cálcio e fosfato 12 .…”
unclassified